2020
DOI: 10.1177/0959353520945857
|View full text |Cite
|
Sign up to set email alerts
|

Pathways and penalties: Exploring experiences of agency among incarcerated women in South Africa

Abstract: Despite the documented rise in the population of incarcerated women over recent decades, female offenders only represent about 5% of the total global incarcerated population. South Africa is no different – female offenders total less than 3% of the country’s incarcerated population, a populace that was previously counted as one of the ten largest correctional systems in the world. This small representation of women in the correctional system leads to interpretations of their pathways to offending and experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
6
1
Order By: Relevance
“…The intersectionality of systemic gender inequality, poverty stratified along gender lines, trauma, gender based violence against women (GBVAW), mental health issues, and marginalisation, prior to incarceration continue to be reflective of their wider positionality in South African society (Haffejee et al, 2005;Community Law Centre, 2007;Artz et al, 2012;Steyn and Booyens, 2018;UNODC, 2019;ARASA, 2019). They have distinct gendered pathways into crime, often heavily underpinned by crimes of survival, with continued gender and race discrimination in prison (du Preez, 2006;Van Hout and Chimbga, 2020;Parry, 2020;Lauwereys, 2021).…”
Section: Insert Table 2 Prementioning
confidence: 99%
See 1 more Smart Citation
“…The intersectionality of systemic gender inequality, poverty stratified along gender lines, trauma, gender based violence against women (GBVAW), mental health issues, and marginalisation, prior to incarceration continue to be reflective of their wider positionality in South African society (Haffejee et al, 2005;Community Law Centre, 2007;Artz et al, 2012;Steyn and Booyens, 2018;UNODC, 2019;ARASA, 2019). They have distinct gendered pathways into crime, often heavily underpinned by crimes of survival, with continued gender and race discrimination in prison (du Preez, 2006;Van Hout and Chimbga, 2020;Parry, 2020;Lauwereys, 2021).…”
Section: Insert Table 2 Prementioning
confidence: 99%
“…The intersectionality of systemic gender inequality, poverty stratified along gender lines, trauma, gender based violence against women (GBVAW), mental health issues and marginalisation, prior to incarceration continue to be reflective of their wider positionality in South African society (Haffejee et al , 2005; Community Law Centre, 2007; Artz et al , 2012; Steyn and Booyens, 2018; UNODC, 2019; AIDS and Rights Alliance for Southern Africa (ARASA), 2019). They have distinct gendered pathways into crime, often heavily underpinned by crimes of survival, with continued gender and race discrimination in prison (du Preez, 2006; Van Hout and Chimbga, 2020; Parry, 2020; Lauwereys, 2021). Many academic critiques of the South African penal system and rights-based commentaries on prisoner human rights since 1994 either ignore women in their entirety, or simply refer to women in the sense of separation of sexes (Bukurura, 2002; de Vos, 2005; Muntingh, 2006).…”
Section: The Nexus Of Gender Race and Incarcerationmentioning
confidence: 99%
“…These findings are corroborated by South African research (Artz et al, 2012;Ackerman, 2014;Haffejee et al, 2005;Parry, 2020). A study conducted by Pretorius and Botha (2009) found that 91% of participants indicated that they had children.…”
Section: Motherhood and Crimementioning
confidence: 57%
“…To sum, considering women's actions and agency as Hays (1997) originally proposed may offer a different, richer perspective (Parry, 2021) than the one currently reflected in IM literature. Such a perspective can also help more accurately reflect women's lived experience in future research, policy formulation, counseling, and other social supports to cater more effectively toward their realities.…”
Section: Discussionmentioning
confidence: 97%